Studies of different growth stages of wood apple (Feronia limonia) through extended BBCH-scale under rainfed semi arid conditions of western India (Current Horticulture, 2024)
Phenology is the study of the timing of recurring biological events like bud breaks, flushing, flowering and fruiting. The  knowledge of the phenology of a particular crop is essential for its managements. The stages of phenology in fruit crops will  promote farm mechanization and improve fruit yield. Phonological stages allow an optimum use farm input at critical and  essential stage of plant. Twenty eight genotypes of wood apple (Feronia limonia L.) were studies were at CHES, ICAR (CIAH),  Godhra during 2017-2019. Eight principal growth stages of wood apple were found in wood apple, starting from vegetative bud  dormancy (stage 0) to maturity of the fruit (stage 8). Three principal growth stages like stage 0, 1 & 3 are denoting to vegetative  growth. Remaining stages (5, 6, 7 & 8) was reported to reproductive growth and development. During investigation, the principle  growth stages were divided in sub categorized called as secondary stages, which denoting the shorter developmental intervals.  The first digit of code in BBCH scale denotes the principle growth stage (0-8) and second digit defined by the meso stages (1 to  n). The third digit is numerical value between 0-9 that refer to percentage development of buds, leaves, shoots, flowering, fruit  development, fruit maturity and senescence.
Keywords: wood apple; semi-arid; development stages; extended BBCH-scale